Development of Service Innovations and Literacy Regarding The Keretaku App to Enhance Customer Satisfaction for Honda Motorcycles at PT Cakra Adi Dharma - Kelvin Kelvin; Pristiyono Pristiyono; Usmala Dewi Siregar (Journal of World Science, 2026)
Almost all companies in marketing and their business, starting from sales and service, make consumer satisfaction as the main variable or key or priority weapon in practice, both in promotional and marketing practices that have an impact on increasing sales. The purpose of this study is to prove the partial and simultaneous influence between the variables of service innovation and literacy of the KERETAKU application on consumer satisfaction. The population in this study is all permanent customers registered with PT Cakra Adi Dharma Rantauprapat from January to May 2025 as many as 231 people and samples from the slovin formula were obtained 146 people. The data analysis tool used in this study is multiple linear regression, where this analysis tool is a statistical tool consisting of Validityand Reliability, Classical Assumption Test, Partial Test (t-Test), Simultaneous Test (F Test) and Coefficient of Determination (R2). From the results  of the respondent profile research, most respondents who visited PT Cakra Adi Dharma Rantauprapat had used the KERETAKU application while others had not used it. Meanwhile, the results of the study partially show that the variable of Service Innovation is a variable that has a very good influence on consumer satisfaction. The literacy variable of the KERETA application partially has no effect on consumer satisfaction. However, simultaneously the variable of Service Innovation and the variable of KERETAKU Application Literacy have a good effect on consumer satisfaction.